Ultrasonic-assisted synthesis and photocatalytic performance of ZnO nanoplates and microflowers - Anukorn Phuruangrat (2018)
© 2016 Elsevier Ltd. Nanoplates, multi-layered nanorod petal flowers and microflowers of nanoneedles with pyramid tips of hexagonal ZnO nanostructures were ultrasonically synthesized in the solutions containing zinc nitrate hexahydrate, ammonium hydroxide and cetyltrimethyl ammonium bromide (CTAB) with pH adjusting to 7-10. The as-synthesized wurtzite hexagonal ZnO was detected by X-ray diffraction (XRD). Fourier transform infrared (FTIR) spectroscopy revealed the standard peak of zinc oxide at 507-518 cm-1, and Raman spectroscopy at 437 cm-1. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to characterize the products with the morphologies of nanoplates, multi-layered nanorod petal flowers and microflowers of nanoneedles with pyramid tips at the pH of 7, 8-9, and 10, respectively. In addition, the photocatalytic degradation of methylene blue (MB) under UV radiation by the hexagonal ZnO nanoplates is the highest at 97.54%.